Identification of Fingerprint Pattern and Lip Print Pattern in Females of Type 2 Diabetes Mellitus as a Biomarker - Smail, Harem Othman; Ahmad, Renas Hama; Jalal, Eman Ibrahim (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Diabetes mellitus (D.M.) is a chronic metabolic disorder that has increased worldwide. Fingerprints and lip prints are noninvasive procedures that are genetically used in criminal cases and to determine genetic disorders such as Diabetes mellitus type 2. Dermatoglyphics is the epidermal ridge configuration, the ridged skin on our fingertips, palms, and toes. There are three types (Whorl, et al.). Cheiloscopy, derived from the Greek word (cheilos), which means lip, is the study of crinkles and grooves that are perceptible on our lips and unique. We conducted our research with 90 females, 45 were with (DMT2), and 45 were normal females over 30 years old. The samples were collected in different Kurdistan regions (Erbil City, Qaladza Town, Koya Town, and Koya University). We collected all 10 (ten) fingerprint patterns and divided them into Whorl, loop, and arch using an ink pad. Also, lip samples were collected by using lipstick on A4 paper. According to our research, the predominant fingerprints and lip prints in females with type 2 diabetes were loops for both hands (right (31.1%) and left (28.4%)), and for lips, the print was intersected grooves (28.9%). The predominant fingerprint and lip print for normal females were also loops in both hands (right (28%) and left (25%)), and the lip print was complete vertical grooves (42.2%). The study showed no association between fingerprint pattern and diabetes mellitus type 2 and cannot be used as a biomarker for it. However, there is a clear association between lip print pattern and diabetes mellitus type 2, and it can be used as a specific biomarker.